Synthesis of branched and linear galactooligosaccharides related to glucuronoxylomannogalactan of Cryptococcus neoformans - Dorokhova, Vera S.; Komarova, Bozhena S.; Previato, José O.; Mendonça Previato, Lúcia; Krylov, Vadim B.; Nifantiev, Nikolay E. (Frontiers in Chemistry, 2024)
Synthesised is a series of oligo-α-(1→6)-D-galactopyranosides bearing β-D-galactofuranosyl residues at O-2 and/or O-3 which relate structurally to fragments of the glucuronoxylomannogalactan (GXMGal) of the Cryptococcus neoformans fungal pathogen causing severe diseases in immunocompromised patients. The preparation of target compounds is based on the use of selectively O-protected N-phenylacetimidoyl galactopyranoside donor with an allyl group at O-2, levulinoyl group (Lev) at O-3, pentafluorobenzoyl (PFB) group at O-4, and fluorenylmethoxycarbonyl (Fmoc) group at O-6. The choice of protecting groups for this donor ensures the stereospecific formation of α-(1→6)-glycosidic bonds due to the stereodirecting effect of acyls at O-3, O-4, and O-6. At the same time, this combination of O-substituents permits the selective recovery of free OH-groups at O-2, O-3, and O-6 for chain elongation via the introduction of β-Dgalactofuranosyl and α-D-galactopyranosyl residues. The reported compounds are obtained as aminopropyl glycosides which were transformed into biotinylated conjugates for further uses as coating antigens in immunological studies. Obtained oligosaccharides were subjected to detail 13 C NMR-study to show spatial similarity of obtained hexasaccharide with corresponding fragment in the GXMGal chain to make this compound suitable for further immunological studies of C. neoformans.